The Effect of Using Skimming Technique in Students Reading Comprehension to Find out Main Idea at The Ninth Grade of Mts TI Paninggahan - Leni Fatimah; Loli Safitri; Widya Syafitri; Syahrul Syahrul (Education Achievement: Journal of Science and Research, 2024)
This research was done due to several problems that found by the researcher. This research was aimed to find out the effect of using skimming technique in students reading comprehension to find out main idea on narrative text. This research was conducted at the ninth grade of Mts Ti Paninggahan. In this study, the researcher used quantitative method with pre-experimental design by comparing the students’ pre-test and post-test scores. To determine the sample, the researcher used purposive sampling and choosed one class as experimental class. The subject of this study ninth grade that consist of 18 students. The data was analyzed using t-test formula. The result shown that there were significant difference on the students reading comprehension to find out main idea after taught used skimming technique. The students mean score of the post-test was 78,33, it is bigger than mean score of pre-test was 46,11. The researcher used t-test formula by comparing score of pre-test and post-test through SPSS. Based on the output statistic, the value of Sig (2-tailed) is 0,00 < 0,05. It means that Ha is accepted. It means that the students who are taught using skimming technique is better than the students who are taught before using skimming technique. In short, skimming technique has a significant effect on students’ reading comprehension to find out main idea on narrative text at Mts Ti Paninggahan.